School-based interventions to promote personal and environmental hygiene practices among children in Pakistan: protocol for a mixed methods study - Nousheen Akber Pradhan; Waliyah Mughis; Tazeen Saeed Ali; Maleeha Naseem; Rozina Karmaliani (BMC, 2020)
Abstract Background Poor personal hygiene and inadequate sanitation practices among young children leads to communicable diseases. There remains a gap in the holistic assessment of school children's hygiene literacy, practices and effectiveness of school-based hygiene interventions in Pakistan. Therefore, a school-based intervention protocol has been designed to promote personal and environmental hygiene practices for primary school children. Towards improving children's hygiene behaviors, the study will also focus on enhancing mothers' hygiene knowledge and practices. Methods Using quasi-experimental design with mixed methods data collection approaches, this study will be conducted in schools located in an urban squatter settlements in Pakistan. To assess primary grade children and their mothers' hygiene status, a survey will be held in the pre-intervention phase. This phase also includes qualitative exploration of key stakeholders (mothers, teachers, health & education authorities representatives') perceptions about the factors facilitating and impeding the adaption of hygiene behaviors among school children. In-depth guides and focus group discussion tools will be used for this purpose. This will be followed by multi-component intervention phase with behavior change strategies to improve children's and mothers' hygiene literacy and behaviors. The post-intervention phase will assess the intervention effectiveness in terms of enhancing hygiene knowledge and practices among school children and mothers, alongside exploration of mothers and teachers' insights into whether or not the intervention has been effective in improving hygiene practices among children. Paired t-test will be applied pre and post-intervention to measure the differences between the mothers and children's hygiene literacy and knowledge scores. Similar test will be performed to assess the differences in children's hygiene knowledge and practice scores, pre and post-intervention (< 50 = poor, 50-75 = good and > 75 = excellent). Thematic analysis will be carried out for qualitative data. Discussion Multi-component intervention aimed at improving personal and environmental hygiene among primary school children offers an opportunity to design and test various behavioral change strategies at school and in home settings. The study findings will be significant in assessing the intervention's effectiveness in improving children's overall hygiene. Trial registration Retrospectively registered with ClinicalTrials.gov ( NCT03942523 ) on 5th May 2019.